The relationship of academic resilience with positive thinking among female students at King Saud University - Al-Khelaiwi, Aeshah Mohammad; Al-Mohammadi, Afaf Salem (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the relationship between academic resilience and positive thinking among female students at King Saud University, and the differences between them in academic resilience and positive thinking in light of the specialization variable. The application of the Academic Resilience Scale prepared by Cassidy (2016) and translated by the researcher on the Saudi environment, and the Positive Thinking Scale prepared by Hadyan (2021). The results of the study found that there is a strong positive correlation with statistical significance at the level of significance (0.01) between academic resilience and positive thinking in each of (the first dimension: perseverance, the second dimension: meditation and adaptation to seek help), while there is an inverse correlation between the third dimension Effects, emotional response, and positive thinking. The general average of the academic resilience scale has an arithmetic mean of (3.66), and a (high) degree of response. Likewise, the general average of the positive thinking scale came with an arithmetic mean of (4.17), and a score of (.528). response (high). The results also revealed that there were no statistically significant differences at the significance level (0.05) between the average scores of the study sample on the scale of academic resilience in all dimensions, as well as the general average due to the variable of specialization, as well as the absence of statistically significant differences at the significance level (0.05) between The average scores of the study sample on the positive thinking scale in all dimensions, as well as the general average, are attributed to the variable of specialization.
Keywords: Academic; Resilience; Positive; Thinking; Relationship; Students